2000
DOI: 10.1002/1097-0142(20000815)89:4<724::aid-cncr2>3.0.co;2-4
|View full text |Cite
|
Sign up to set email alerts
|

Distinction of differentiated type early gastric carcinoma with gastric type mucin expression

Abstract: BACKGROUND Intestinal and diffuse gastric carcinomas differ in morphology and growth behavior. Differentiated type gastric carcinoma (DGC), which corresponds roughly with the intestinal type of Lauren, can demonstrate phenotypic properties associated with mucin expression and brush border. However, their clinical significance is controversial. A classification based on mucin phenotype and brush border was performed to determine the clinicopathologic diversity of DGCs in their early stage. METHODS A total of 12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
97
3
2

Year Published

2002
2002
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 126 publications
(108 citation statements)
references
References 27 publications
(23 reference statements)
6
97
3
2
Order By: Relevance
“…In our cohort, papillary EGCs, compared to tubular EGCs, show significantly deeper invasion into the submucosal layer, more frequent association with a micropapillary component, and probably more frequent lymphovascular invasion, although the p value for lymphovascular invasion was 0.059. These results are parallel to those of the previous similar studies on papillary EGC from Japan 18,19 and Korea 13, in which submucosal invasion was reported to be over 20% 13, and lymphovascular invasion was found in over 28% in Korean patients 13 and over 70% in Japanese patients 18. Importantly, the nodal metastasis rate is alarmingly high and discovered in 13.6% of the current cohort and over 18% in a Korean study and 18.2% - 29.2% in two Japanese studies 18,19, which is significantly higher than that of non-papillary EGCs 13,19, including tubular EGCs as shown in this report.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In our cohort, papillary EGCs, compared to tubular EGCs, show significantly deeper invasion into the submucosal layer, more frequent association with a micropapillary component, and probably more frequent lymphovascular invasion, although the p value for lymphovascular invasion was 0.059. These results are parallel to those of the previous similar studies on papillary EGC from Japan 18,19 and Korea 13, in which submucosal invasion was reported to be over 20% 13, and lymphovascular invasion was found in over 28% in Korean patients 13 and over 70% in Japanese patients 18. Importantly, the nodal metastasis rate is alarmingly high and discovered in 13.6% of the current cohort and over 18% in a Korean study and 18.2% - 29.2% in two Japanese studies 18,19, which is significantly higher than that of non-papillary EGCs 13,19, including tubular EGCs as shown in this report.…”
Section: Discussionsupporting
confidence: 92%
“…Although both papillary and tubular EGC tumors are believed to be similar in prognosis and risk of nodal metastasis 6, the recent investigations from others and ours show the results otherwise 9,13,18. We demonstrated several significant differences in the present comparison study between these two groups of EGC in prognosis-associated risk factors, such as significantly older patient age, more frequent proximal gastric location, and more common association with a micropapillary component, in addition to deeper invasion and higher frequency of lymphovascular, nodal, and distant metastases, as aforementioned.…”
Section: Discussionmentioning
confidence: 47%
See 1 more Smart Citation
“…Furthermore, we also performed IHC staining and extensively examined E-cadherin, b-catenin, VEGF, p53, and Ki-67 expression levels. Although previous studies have not shown consistent results in respect to mucin phenotype expression and its relationship with the histological type of gastric cancer, the available data suggest that mucin phenotype is related to invasiveness, recurrence, and prognosis [2,11,17,21,22]. Our phenotyping data suggested that TAC was associated with intestinal metaplasia [11], but that PCC was derived from gastric mucosa de novo [23].…”
Section: Discussioncontrasting
confidence: 46%
“…E-cadherin maintains intercellular adhesion and is connected to b-catenin and the actin cytoskeleton. Downregulation of E-cadherin and b-catenin decreases the ability of cells to adhere to each other, which induces their detachment from the primary tumor, leading to infiltration into surrounding tissues [21,25,27,28]. Several familial gastric cancers are associated with inactivation of the E-cadherin gene causing loss of cell adhesion [29].…”
Section: Discussionmentioning
confidence: 99%